Assessment of Target Mean Compressive Strength of Concrete Using Seti River Aggregates in Pokhara, Nepal - Banstola, Ramesh; GC, Santosh; Koirala, Sudeep (Technical Journal, 2025)
The sound properties of the coarse and fine aggregate play vital roles in achieving the strength and durability of the concrete. The physical and mechanical properties of aggregate were tested as per the Indian Standard (IS) and the Standard Specification for Road and Bridge Works (SSRBW). The test results reveal that all three sources in the Seti River from where aggregates were extracted satisfy the IS code provisions for standard concrete mix design. The standard concrete of M35 and M45 grade with the mix design was carried out, but the source of sample C does not meet the target mean compressive strength of M45 grade concrete as per Indian Standard. According to the Department of Roads Specification, only source A meets the target mean compressive strength, whereas sources from B and C do not meet the target mean compressive strength for M45 grade concrete. The geological origin of aggregate & mixture proportioning adjustment should be carried out to improve target mean compressive strength for M45 grade concrete of sample source C.